Karakteristik Perusahaan Terhadap Luas Pengungkapan Corporate Social Responsibility - Aryo Prakoso; Aulia Ayu Dewinta (Faculty of Economic and Business, 2019)
Globalization provides open competition to every business actor, to become a superior and valuable company one of the ways that can be taken by the company through disclosure of the corporate social reports (CSR). This paper wants to explore how far the characteristics of the company influence the extent of CSR disclosure. The method in this study uses the empirical study hypothesis testing approach by sampling all companies indexed L-Q45 on the Indonesia stock exchange. The reason selection of this index is the leading index in Indonesia with tightly defined criteria by regulators, including levels of liquidity, market capitalization, and growth prospects of the company. The results of the data analysis that has been done obtained results Profitability and total assets influence the broad disclosure of CSR, this also supports stakeholder theory and legitimacy theory, on the contrary, leverage does not affect the broad disclosure of CSR. That caused by the management of the company seeing high leverage tends to reduce the disclosure of social responsibility so as not to be in the spotlight of the debtholders